Old-time religion embracing modernist culture : American fundamentalism between the wars - Abrams, Douglas Carl, 1950- (Lexington Books, 2017)
American fundamentalism, for decades depicted as alienated from society, has garnered the attention of historians, whose studies have shown a more complex movement. This book, targeting the founding generation, seeks to understand their resilience, since their beginning through their adaptation to modernist culture.